Genetics and the Individualized Therapy of Vestibular Disorders - Mei, Christine; Dong, Hongsong; Nisenbaum, Eric; Thielhelm, Torin; Nourbakhsh, Aida; Yan, Denise; Smeal, Molly; Lundberg, Yesha; Hoffer, Michael E.; Angeli, Simon; Telischi, Fred; Nie, Guohui; et al. (Frontiers in Neurology, 2021)
Background: Vestibular disorders (VDs) are a clinically divergent group of conditions that stem from pathology at the level of the inner ear, vestibulocochlear nerve, or central vestibular pathway. No etiology can be identified in the majority of patients with VDs. Relatively few families have been reported with VD, and so far, no causative genes have been identified despite the fact that more than 100 genes have been identified for inherited hearing loss. Inherited VDs, similar to deafness, are genetically heterogeneous and follow Mendelian inheritance patterns with all modes of transmission, as well as multifactorial inheritance. With advances in genetic sequencing, evidence of familial clustering in VD has begun to highlight the genetic causes of these disorders, potentially opening up new avenues of treatment, particularly in Meniere’s disease and disorders with comorbid hearing loss, such as Usher syndrome. In this review, we aim to present recent findings on the genetics of VDs, review the role of genetic sequencing tools, and explore the potential for individualized medicine in the treatment of these disorders. Methods: A search of the PubMed database was performed for English language studies relevant to the genetic basis of and therapies for vestibular disorders, using search terms including but not limited to: “genetics,” “genomics,” “vestibular disorders,” “hearing loss with vestibular dysfunction,” “individualized medicine,” “genome-wide association studies”, “precision medicine,” and “Meniere’s syndrome.” Results: Increasing numbers of studies on vestibular disorder genetics have been published in recent years. Next-generation sequencing and new genetic tools are being utilized to unearth the significance of the genomic findings in terms of understanding disease etiology and clinical utility, with growing research interest being shown for individualized gene therapy for some disorders. Conclusions: The genetic knowledge base for vestibular disorders is still in its infancy. Identifying the genetic causes of balance problems is imperative in our understanding of the biology of normal function of the vestibule and the disease etiology and process. There is an increasing effort to use new and efficient genetic sequencing tools to discover the genetic causes for these diseases, leading to the hope for precise and personalized treatment for these patients.